Advances in intestinal microecology in colorectal cancer and its immunotherapy - Zhao Jiaying; Zhang Ruyi; Zheng Yi; Shao Zheng; Fang Weijia (结直肠肛门外科)
Intestinal microecology affects the occurrence and development of cancer and the efficacy of immunotherapy. So far, most studies were animal experiment research focusing on molecular mechanisms or limited to the correlation between intestinal microecology and cancer responses to immunotherapy. There is still a lack of interventional clinical trials in a large sample and research elucidating the synergistic effect of diverse, effective bacterial groups on the cancer responses to immunotherapy. This article focused on the advances in intestinal microecology in colorectal cancer and its immunotherapy. We summarized the findings from current relevant basic and translational research. We aimed to provide valuable insight into this hot topic field and its future direction.